The overexpression of scaffolding protein NEDD9 promotes migration and invasion in cervical cancer via tyrosine phosphorylated FAK and SRC. - Ni Sima; Xiaodong Cheng; Feng Ye; Ding Ma; Xing Xie; Weiguo Lü (PLoS ONE, 2013)
NEDD9, a focal adhesion scaffolding protein, has been recently proposed to regulate invasion and metastasis in some cancer types, but unknown in cervical cancer. The aim of this study was to determine if NEDD9 was involved in the progression and metastasis of cervical cancer. The experimental results showed NEDD9 protein was overexpressed in cervical cancer compared with normal cervical epithelium tissues. Overexpression of NEDD9 was correlated with histological grading, lymph node metastasis, and FIGO stage of cervical cancer. Silencing NEDD9 resulted in tyrosine dephosphorylation of FAK and SRC oncoproteins, and decreased cell migration and invasion in the cervical carcinoma SiHa and HeLa cells. Overexpression of NEDD9 led to tyrosine phosphorylation of FAK and SRC oncoproteins, and increased cell migration and invasion. Moreover, tyrosine phosphorylation of NEDD9 was significantly decreased via suppressing tyrosine phosphorylation of FAK or SRC, suggesting a positive feedback loop of tyrosine phosphorylation between NEDD9 and FAK or SRC. In addition, our data showed that silencing NEDD9 decreased Vimentin expression and increased E-cadherin expression in cervical cancer cells, and vice versa. E-cadherin was subject to regulation of NEDD9, FAK and SRC, but altered neither tyrosine-phosphorylated nor total NEDD9. Our findings suggest that NEDD9 is overexpressed in cervical cancer tissues and cells, and overexpressed NEDD9 promotes migration and invasion in cervical carcinoma cells, probably via a positive feedback loop of tyrosine phosphorylation between NEDD9 and FAK or SRC.